(untitled) (Mustansiria Dental Journal, 2019)
The aim of this in vitro study was to compare the effect of different Nickel Titanium instruments on the root dentin in term of dentinal defects. Seventy-five palatal roots of maxillary first molars teeth were selected for the study. Fifteen roots were left unprepared to serve as a negative control group; the remaining 60 roots were divided into four tested groups. Group (I) prepared using ProTaper Universal, group (II) prepared by EndoSequence, Group (III) prepared by ProTaper Next and finally group (IV) prepared by RECIPROC systems. After preparation the roots were embedded in clear acrylic and then sectioned at different levels (apical, middle and coronally) and examined under Stereomicroscope. Results: No cracks were observed in the negative control group, while dentinal defects were observed in roots prepared with ProTaper Universal, EndoSequence, ProTaper Next and RECIPROC systems (28.88%, 8.89%, 11.11% and 33.33% respectively). The results showed a non-significant difference between EndoSequence and Protaper Next groups and between ProTpaer Universal and RECIPROC groups (p > 0.05), ProTaper had a significant difference with EndoSequence and ProTaper Next groups (P < 0.05) While The RECIPROC group had a highly significant difference with EndoSequence and ProTaper Next groups (P < 0.01). Conclusion, all instrumentation systems used in this study created cracks in the root dentin. The EndoSequence and ProTaper Next instruments tended to cause least dentinal cracks compared with the ProTaper Universal and RECIPROC instruments.